2017
DOI: 10.18632/oncotarget.19653
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and immune features of resectable malignant brainstem gliomas

Abstract: We surveyed common genetic mutations (IDH1, H3F3A, PPM1D, and TP53) and immune features (PD-L1 expression and CD8+ T cell tumor infiltration) in a series of 62 malignant brainstem gliomas that were resected via microsurgery. IDH1 mutations were mutually exclusive with H3F3A mutations. IDH1 mutations appeared only in adults and occurred more frequently in tumors larger than 10cm3 (8/29 vs 1/32, Fisher’s exact test, p=0.010). H3F3A mutations occurred more frequently in children and adolescent patients (19/24 vs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…This is a challenge given that these patients represent approximately 10%–15% of an already rare disease; however, international collaborative trials groups (such as those in HERBY represent), already recruit hypermutator and MAPK-altered HGGs in this population for appropriately targeted therapies ( NCT02992964 , NCT02684058 ). Equally importantly, the histone H3 mutant subgroups, which represent a substantial proportion of patients in this age group ( Mackay et al., 2017 ) were found to be very poorly immunogenic, confirming a previous study in resectable malignant brainstem gliomas in children and adults with K27M mutations ( Zhang et al., 2017 ), and further negating the likelihood of clinical response to such therapies.…”
Section: Discussionsupporting
confidence: 84%
“…This is a challenge given that these patients represent approximately 10%–15% of an already rare disease; however, international collaborative trials groups (such as those in HERBY represent), already recruit hypermutator and MAPK-altered HGGs in this population for appropriately targeted therapies ( NCT02992964 , NCT02684058 ). Equally importantly, the histone H3 mutant subgroups, which represent a substantial proportion of patients in this age group ( Mackay et al., 2017 ) were found to be very poorly immunogenic, confirming a previous study in resectable malignant brainstem gliomas in children and adults with K27M mutations ( Zhang et al., 2017 ), and further negating the likelihood of clinical response to such therapies.…”
Section: Discussionsupporting
confidence: 84%
“…Xue et al (2017a) reported that the PD-L1 expression levels positively correlated with the grades of gliomas. Wang et al (2016) and Zhang et al (2017) reported that PD-L1 expression was much higher in GBM compared to grade II and III gliomas. Garber et al (2016) found that the high expression level of PD-L1 (IHC) was positively associated with only grade IV gliomas, though high PD-L1 expression could also be detected in other grades of gliomas.…”
Section: The Expression and Subcellular Distribution Of Pd-l1 In Humamentioning
confidence: 99%
“…Importantly, several recent studies reported that expression levels of PD-L1 are positively correlated with glioma grades (Garber et al, 2016; Wang et al, 2016; Xue et al, 2017a; Zhang et al, 2017). Xue et al (2017a) reported that the PD-L1 expression levels positively correlated with the grades of gliomas.…”
Section: The Expression and Subcellular Distribution Of Pd-l1 In Humamentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study on pediatric cancers, Majzner et al observed PD‐L1 expression in 36% of pediatric GBMs and raised the prospect of a similar immunobiology in pediatric GBM, despite differing oncologic profiles. Zhang et al in 2017, in a study of 62 brainstem gliomas detected a high prevalence of PD‐L1 staining (59.7%). However, the dominant pattern of PD‐L1 staining was cytoplasmic and typically disperse.…”
Section: Discussionmentioning
confidence: 96%